Exploring the Perceptions of Student-Athletes Leading Towards Physical Activity and Perceived Performance - Syamsul Gultom; Dewi Endriani; Agustin Sastrawan Harahap; B. Baharuddin; Hesti Fibriasari (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Student-athletes perceived physical and psychological stability is a vital source of enhanced performance and physical activity. The current study, grounded in attribution theory, examines the effect of student-athletes' reported mental and physical health on their perceived performance and physical activity. Additionally, a unique construct, perceived physical self-concept, is also accessed as an Intervening mechanism between the study variables. A cross-sectional field survey was undertaken of 279 student-athletes enrolled in several Indonesian universities in the Bali area. Perceived psychological and physical health were found to be positively linked with perceived performance and physical activity. Additionally, these associations were found to be mediated by perceived physical self-concept. Further, future research directions, key policy insights, and theoretical and managerial implications for sports science scholars and policymakers are suggested.